Gas production mechanism of Irgamet 39 and its long‐term corrosion resistance - Huiying Xiang; Yuan Yuan; Guoyong Liu; Xue Gao; Cheng Zhang; Jiang Zhou; Ruijin Liao (High Voltage, 2023)
Abstract The phenomenon of transformer failure caused by oil‐sulphur corrosion of oil₋paper insulation system has always been concerned by scholars. Irgamet 39 is the most used metal passivator for inhibiting sulphur corrosion. However, Irgamet 39 causes abnormal dissolved gas in oil during the process of exerting anti‐corrosion effect. Herein, the gas production mechanism of Irgamet 39 and its long‐term corrosion resistance were investigated. Compared with other metal passivators, the Irgamet 39 produces more dissolved gases in oil, especially H2, CO and CO2. The main sources of free radicals in the gas production process are from the branched chains of the Irgamet 39 structure (−CH2N(C8H17)2 and −CH3). Furthermore, the ageing products of insulating paper and oil promote the cleavage of the chain in the Irgamet 39 molecule, which then causes Irgamet 39 to generate more dissolved gases. Irgamet 39 exhibits excellent long‐term corrosion inhibition properties,while it also leads to abnormal gases in the oil, which can affect the interpretation of the dissolved gas analysis data and thus interfere with the diagnosis. This work provides useful information for the practical application of Irgamet 39 and helps electrical workers make reasonable predictions for transformer problems.